2020
DOI: 10.1038/s41598-020-59392-7
|View full text |Cite
|
Sign up to set email alerts
|

Incretin accelerates platelet-derived growth factor-BB-induced osteoblast migration via protein kinase A: The upregulation of p38 MAP kinase

Abstract: Incretins, including glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP), secreted from enteroendocrine cells after food ingestion, are currently recognized to regulate glucose metabolism through insulin secretion. We previously demonstrated that platelet-derived growth factor-BB (PDGF-BB) induces the migration of osteoblast-like MC3T3-E1 cells through mitogenactivated protein (MAP) kinases, including p38 MAP kinase. In the present study, we investigated whether or not incret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…The scratch assay revealed a significant enhancement in the migration of MC3T3-E1 cells following P-GM-2 treatment (Figure J–K). Similar to the findings of this study, previous study has demonstrated that incretins facilitate bone repair by expediting the migration of osteoblasts . The findings suggested that P-GM-2 significantly enhanced the growth, differentiation, and mineralization of osteoblasts, implying its potential role in regulating bone formation through osteogenic activity.…”
Section: Resultssupporting
confidence: 90%
“…The scratch assay revealed a significant enhancement in the migration of MC3T3-E1 cells following P-GM-2 treatment (Figure J–K). Similar to the findings of this study, previous study has demonstrated that incretins facilitate bone repair by expediting the migration of osteoblasts . The findings suggested that P-GM-2 significantly enhanced the growth, differentiation, and mineralization of osteoblasts, implying its potential role in regulating bone formation through osteogenic activity.…”
Section: Resultssupporting
confidence: 90%
“…Also, PI3K and MAPK were requisite in PDGF-BB-mediated MSC motility toward glioma [ 26 ]. Previous studies on osteogenic MC3T3-E1 cells showed that the mitogenic response stimulated by PDGF-BB was dependent on extracellular signal-regulated kinase (Erk) and JNK, whereas the migratory response involved MAPK and JNK [ 27 ]. JNK was further verified with significance in PDGF-induced proliferation and migration of MSCs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, DPP‐IV is a protease that cleaves dipeptides specifically from proteins and oligopeptides after the penultimate N‐terminal cleavage of proline or alanine 37 . DPP‐IV is involved in the degradation of a number of neuropeptides, peptide hormones, and cytokines, including incretins GLP‐1 and GIPs 38 . When glucose is ingested, GLP‐1 and GIPs are rapidly degraded by DPP‐IV.…”
Section: Discussionmentioning
confidence: 99%